Household item ownership and self-rated health: material and psychosocial explanations - Rose Richard; Bobak Martin; Pikhart Hynek; Marmot Michael (BMC, 2003)
Abstract Background There has been an ongoing debate whether the effects of socioeconomic factors on health are due to absolute poverty and material factors or to relative deprivation and psychosocial factors. In the present analyses, we examined the importance for health of material factors, which may have a direct effect on health, and of those that may affect health indirectly, through psychosocial mechanisms. Methods Random national samples of men and women in Hungary (n = 973) and Poland (n = 1141) were interviewed (response rates 58% and 59%, respectively). The subjects reported their self-rated health, socioeconomic circumstances, including ownership of different household items, and perceived control over life. Household items were categorised as "basic needs", "socially oriented", and "luxury". We examined the association between the ownership of different groups of items and self-rated health. Since the lists of household items were different in Hungary and Poland, we conducted parallel identical analyses of the Hungarian and Polish data. Results The overall prevalence of poor or very poor health was 13% in Poland and 25% in Hungary. Education, material deprivation and the number of household items were all associated with poor health in bivariate analyses. All three groups of household items were positively related to self-rated health in age-adjusted analyses. The relation of basic needs items to poor health disappeared after controlling for other socioeconomic variables (mainly material deprivation). The relation of socially oriented and luxury items to poor health, however, persisted in multivariate models. The results were similar in both datasets. Conclusions These data suggest that health is influenced by both material and psychosocial aspects of socioeconomic factors.